2019
DOI: 10.5194/acp-19-1059-2019
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous ice nucleation on dust particles sourced from nine deserts worldwide – Part 2: Deposition nucleation and condensation freezing

Abstract: Abstract. Mineral dust particles from deserts are amongst the most common ice nucleating particles in the atmosphere. The mineralogy of desert dust differs depending on the source region and can further fractionate during the dust emission processes. Mineralogy to a large extent explains the ice nucleation behavior of desert aerosol, but not entirely. Apart from pure mineral dust, desert aerosol particles often exhibit a coating or are mixed with small amounts of biological material. Aging on the ground or dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 88 publications
1
31
0
1
Order By: Relevance
“…Frequently, for added emphasis, the term is given as active site density and denoted as n s . This quantity has already seen extended use in the literature (e.g., Connolly et al, 2009;Niedermeier et al, 2015;Beydoun et al, 2016;Paramonov et al, 2018;Boose et al, 2019). As stated in Sect.…”
Section: Active Site Densitymentioning
confidence: 90%
“…Frequently, for added emphasis, the term is given as active site density and denoted as n s . This quantity has already seen extended use in the literature (e.g., Connolly et al, 2009;Niedermeier et al, 2015;Beydoun et al, 2016;Paramonov et al, 2018;Boose et al, 2019). As stated in Sect.…”
Section: Active Site Densitymentioning
confidence: 90%
“…Hence, historically icenucleation studies have focused on the clay group of minerals (e.g. Broadley et al, 2012;Murray et al, 2011;Wex et al, 2014;Mason and Maybank, 1958;Pinti et al, 2012;Roberts and Hallett, 1968;Hoose and Möhler, 2012). However, more recent work shows that K-rich feldspars (K-feldspars) are very effective INPs when immersed in supercooled water (Whale et al, 2017;Zolles et al, 2015;Tarn et al, 2018;Peckhaus et al, 2016;DeMott et al, 2018;Reicher et al, 2018;Harrison et al, 2016;Niedermeier et al, 2015;Atkinson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins in bacteria are ice nucleation active sites and are well protected when bacteria adhere to mineral dust surfaces (Conen et al, 2011). The attachment of bacteria to dust particles possibly increases the number of sites for ice nucleation and consequently the ice nucleation ability of dust particles (Boose et al, 2019;Conen et al, 2011). The present results show that up to one-tenth or more dust particles could be bacteria carriers, and the concentration of particle-attached bacteria, i.e., the number of bacteria-dust contact sites in dust episodes, was on average 3 times larger than that during nondust periods ( Table 1).…”
Section: Ice Cloud Formationmentioning
confidence: 99%
“…The cooccurrence of dust and high concentrations of bacteria has been observed frequently in different locations, indicating the widespread nature and dissemination of bacteria with dust at local, regional and even global scales (Griffin, 2007;Hara and Zhang, 2012;Iwasaka et al, 2009). Limited available observations have revealed the coexistence of mineral and biological contents in ice crystals (Creamean et al, 2013;Pratt et al, 2009), and laboratory experiments have demonstrated that the ice nucleation ability of dust particles is enhanced by biological components, including bacteria in the particles (Boose et al, 2019;Tobo et al, 2019;Conen et al, 2011). Recent toxicological studies with mouse exposure found that the internal mixture of dust and pathogenic bacteria exacerbated pneumonia (He et al, 2012).…”
Section: Introductionmentioning
confidence: 99%